National survey of prevalence and prognosis of thanatophoric dysplasia in Japan. Issue 8 (27th August 2019) - Sawai, Hideaki; Oka, Kaname; Ushioda, Mariko; Nishimura, Gen; Omori, Takashi; Numabe, Hironao; Kosugi, Shinji
Abstract: Background: Thanatophoric dysplasia (TD) is a rare congenital disease of the skeletal system, with an incidence of 1.68–8.3 per 100 000 births, but statistical data on the estimated number of TD patients across Japan are not available. The aim of this study was therefore to investigate the prevalence and prognosis of TD in Japan. Methods: A nationwide primary questionnaire survey was conducted. Results: A total of 127 obstetric, 186 pediatric, and 115 orthopedic facilities provided responses. Excluding duplications, we identified 73 patients with TD. Of the 73 cases, 15 were abortions, four were stillbirths, 51 were live births, and three had unknown details. Of the 51 live newborns, 27 died ≤7 days after birth, with an early neonatal mortality rate of 56%. Of the 24 newborns who survived the early neonatal period, 16 survived for ≥1 year. All of the 24 newborns received respiratory management and survived during the early neonatal period. Of the 51 live newborns, 25 did not receive respiratory management and died ≤2 days after birth. Conclusions: The prevalence of TD in Japan is estimated to be at 1.1 (95%CI: 0.84–1.37) per 100 000 births, but the actual incidence is expected to be higher. To our knowledge, we have confirmed for the first time that newborns with TD may not always die during the early neonatal period but can survive the early neonatal period with appropriate respiratory management. Therefore, the term "thanatophoric dysplasia" does not accurately reflect the nature of the disease.